Subordinate Justice to Forensic Scientists: Indonesia's Authority and Regulation Gap - Prasetya, Muhammad Djaelani; Ilyas, Amir; Saraka, Erwin Mansyur Ugu; Ratnawati (Universitas Airlangga, 2026)
Abstract This study confirms the existence of fundamental contradictions in the application of Forensic Science in the Indonesian Criminal Justice System (CJS). Although globally recognized as a vital instrument for uncovering material truth and ensuring accountability, its status within Indonesia's legal framework, including the newly promulgated KUHAP 2025, remains implicit, partial, and subordinate to the judiciary. An analysis of regulations and verdict studies (murder, narcotics, and poisoning cases) shows that the Criminal Code reduces the value of forensic scientific evidence to indicative evidence, not explicit or primary evidence. Institutionally, regulation is still centered on Forensic Medicine, ignoring other Forensic Scientist disciplines (such as DNA and Toxicology). This gap is exacerbated by inconsistencies in expert qualifications in field practice, indicating a human resource crisis and the absence of comprehensive standards. The attachment of forensic institutions exclusively to the police creates a serious challenge to their independence and impartiality. Doctrinally, these findings demand the transformation of Forensic Science's position from a mere tool to an essential component that is mandatory and independent. This demand requires the explicit integration of Forensic Science as a strong type of evidence in the Criminal Code and the establishment of procedural standards and codes of ethics to ensure a scientific, objective, and effective evidentiary process to prevent the risk of human rights violations.